Judicial Control and Prosecutorial Supervision in the System of Guarantees for Observing the Rights and Freedoms of a Suspect Person - DYUSSEBAYEV, Talgat T.; AMANGELDY, Aizhan A.; BALASHOV, Talgat T.; AKIMBAYEVA, Ainur A.; ARATULY, Kuanysh; TELEUYEV, Galym B. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).12, 2020)
In the process of reforming the criminal procedure legislation, the institution of the prosecutor’s office has become one of its important aspects. The judiciary, being one of the independent and autonomous branches of power in criminal proceedings, which is a system of protecting the rights and freedoms of citizens, is by far the most effective structure for protecting human rights. The article reveals the essence of judicial control and prosecutorial supervision, identifies a number of problems in the form of potential threats to ensure the rights and legitimate interests of a suspect (accused) in this form of preliminary investigation. As a result of the study, the following was stated. The current provisions of the CIS constitutions regulating the sphere of human rights and freedoms have made it possible to single out separate independent areas in the activities of the prosecutor’s office. Based on the practical problems that arise in the conditions of the new Criminal Procedure Code in the CIS countries, the authors consider it reasonable that the current oversight functions assigned to the prosecution authorities in ensuring the rights and freedoms of a suspect and an accused during the investigation, necessitate further special studies with the aim of development of evidence-based proposals for their resolution.